Antitumoral effect of the aqueous extracts of Bomarea cornigera (Alstroe- meriaceae) on the sarcoma induced in mice - Villanueva, Christian (2010)
We investigated antitumor effect of aqueous extract of Bomarea cornigera. Swiss albino mice strain were inoculated with tumor cell line TG-180 for 15 days, after which they were separated into 5 groups (n= 5 per group). Cyclophosphamide was administered intraperitoneally (positive control), distilled water (negative control) and the aqueous extract at concentrations of 1X, 2X and 4X; the morbidity, mortality, weight and length of the sarcoma were assessed. We found an inhibitory effect of extract of B. cornigera in the development of solid tumor in mice where the TG-180 sarcoma was transplanted. The inhibition rates were 87.44 and 8.52% after 17 days of treatment, considering 1X dose (lowest) and 2X (intermediate), respectively. These results suggest that administration of aqueous extract of B. cornigera intraperitoneally may be useful as a cancer inhibitor.